The Right to Universal Accessibility - de Asís Roig, Rafael (The Age of Human Rights Journal, 2023)
This paper presents universal accessibility from a human rights perspective. This approach provides a comprehensive view of universal accessibility, which can be considered as a specific right or as part of the essential content of any right. Despite its self-evident justification, this right is not legally recognized.